Psychosocial factors contributing to the burden of Informal caregivers of people living with alzheimer’s in Bogotá (2025)
This study examines psychosocial factors contributing to caregiver burden and decreased subjective well-being among informal caregivers of people living with Alzheimer’s disease in Bogotá, Colombia. The research aimed to identify which caregiver- and patient-related variables most significantly influence perceived burden and well-being. A total of 107 informal caregivers were recruited and categorized into three socioeconomic groups based on monthly income. Data were collected through validated instruments measuring caregiver burden, life satisfaction, psychological well-being, positive and negative affect, and psychosocial variables (e.g., anxiety, depression, loneliness, positive aspects of caregiving, mental and physical health). Patient characteristics were also assessed using measures such as the Barthel Index, Clinical Dementia Rating, and Neuropsychiatric Inventory. Results showed that 74.77% of participants experienced caregiver burden, with a higher burden reported in lower socioeconomic groups. Significant differences in burden, well-being, and negative affect were found between socioeconomic groups, highlighting inequality in caregiving experiences. Regression analyses revealed that caregiver burden was primarily predicted by psychosocial variables, notably being female and having higher anxiety levels. Life satisfaction was positively predicted by mental health and positive caregiving perceptions, and negatively by loneliness and cognitive functioning. Negative affect was predicted by female gender and anxiety, while positive affect was not significantly predicted by psychosocial factors. Psychological well-being was positively predicted by positive caregiving perceptions, socioeconomic status, education, and mental health, and negatively by loneliness, depression, and cognitive functioning. Among patient-related variables, only neuropsychiatric symptoms significantly predicted caregiver burden. Regarding positive affect, greater patient independence and higher dementia severity were associated with lower positive affect in caregivers, while more severe neuropsychiatric symptoms had a paradoxical positive association. No patient-related variables significantly predicted life satisfaction or psychological well-being. These findings emphasize the need for caregiver-centered interventions, especially in lower-income settings, that address anxiety, loneliness, gender disparities, and promote positive meaning in caregiving.